Can aromaticity be a kinetic trap? Example of mechanically interlocked aromatic [2-5]catenanes built from cyclo[18]carbon. Issue 18 (5th February 2020) - Fedik, Nikita; Kulichenko, Maksim; Steglenko, Dmitriy; Boldyrev, Alexander I.
Abstract : Aromaticity serves as a kinetic trap for mechanically interlocked cyclo[18]carbon rings. Abstract : The unusual stability of cyclo[18]carbon arising from its aromaticity might be used to provide the kinetic trapping needed in the design of interlocked systems. The kinetic barrier separating the interlocked rings and the chemically bonded complex is about 30 kcal mol −1 . In addition, the rings can slide freely, which is a promising property for the design of molecular gears and motors.